Surface Modification of Silica Gel by Interfacial Polyelectrolyte Complexes - Yongjun Zhang; Weixiao Cao (Adsorption Science & Technology)
Two types of modified silica gel have been prepared by constructing layers of a thermolabile interfacial polyelectrolyte complex on the surface of silica gel using diazo resin (DR) as the polycation and poly(sodium styrene sulphonate) (PSS) as the polyanion. Dye adsorption from aqueous solution was employed to estimate the surface properties of the silica gels. It is believed that the diazo resin is anchored on the surface of the silica gel after thermal treatment through covalent bond formation. The adsorption ability of the surface for cationic dyes increases after such modification. Anionic dyes, which cannot be adsorbed by the unmodified silica gel, can be adsorbed by the modified ones. This indicates that a hydrophobic surface has been built up on the silica gel.